Memahami Makna Bakhil dalam Al-Quran dan Hadis - Prabowo, Yudhi (ANWARUL, 2022)
Islam is a religion that places great emphasis on people giving away their wealth in a good way, so that generosity arises which is one of the main characteristics that every Muslim individual who hopes for success in life and his life needs to always have, grow and develop. However, there is a trait and characteristic that can destroy generosity and the root of compassion, that can hide itself in the human subconscious to abandon good morals, that is known as miserliness. Miserliness paved the way for human nature to abandon its good morals. This research study is entirely based on literature review or literature studies. Therefore, the nature of the research is library (Library Research). The data collected and analyzed all come from literature and other document materials, such as books, writings in journals, as well as in other media, which are relevant to the problem under study. so you get the right answer. First, the word expression derived from the word (بخل) in the Qur'an is mentioned 12 times in 6 letters. Second, there are many things explained in the Qur'an in response to miserly acts, including encouraging sacrifices with one's soul, sacrificing property in jihad, Allah says about various kinds of harsh threats against miserly people, and stinginess is an illustration of shirk. who have loved excessive wealth than loving God. arrogance and turning away from the truth. The emergence of miserliness which is human nature due to driving factors such as the environment and education, love of the world and fear of poverty, being arrogant, money is the goal of life, and neglecting the effects of stinginess.